Mengabdikan Hidup sebagai Pelayan Tuhan: Biografi Rosalina Kusnohardjono - Ivony, Ivony; Witrianto, Witrianto (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2023)
This article focuses on writing the biography of Rosalina Kusnohardjono and aims to reveal her life as a nun through descriptive narrative. The research employs a historical method consisting of four stages: heuristics, source criticism, interpretation, and historiography. The first stage involves searching and collecting historical sources, including primary and secondary sources such as archives, photos, and interviews with Rosalina. The second stage entails filtering and evaluating the historical sources using internal and external criticism. The third stage is the analysis and interpretation of the sources, and the fourth stage is the writing of history based on the data obtained. Rosalina Kusnohardjono, a nun from the SCMM congregation, was originally from a Buddhist background but converted to Catholicism during high school. She entered the SCMM congregation on February 19, 1969, and became a permanent member on February 11, 1979. During her 50 years as a nun, she served as a teacher, SCMM provincial, and founded 15 SCMM communities in Indonesia, including two in Timor Leste. She also established the St. Leo Padang orphanage, a place of prayer and pilgrimage called